The Elusive Johann Joseph Oppel (1815–1894). (September 2014) - Phillips, David; Wade, Nicholas J
Oppel is frequently cited for coining the term 'geometrical optical illusions' in 1855, but portrayals of him have rarely been sighted. We present a portrait of him and a brief description of his contributions to the study of illusions as well as other areas of sound and vision, particularly stereoscopy, colour, and motion. Despite the citations in the context of illusions, Oppel remains an elusive figure in the history of science.